THE EFFECT OF WORK ENVIRONMENT, SERVICE, CUSTOMER SATISFACTION ON EMPLOYEE PERFORMANCE AT COFFEE SHOP GEKO MEDAN CITY - Alisahelga Ivana Meliala; Muhammad Alfaredo Tarigan; Kiki Rizky Priwanda Putri; Deni Faizal Mirza; Muhammaad Fadlan Mirza; Nurlina Harahap (CV. Radja Publika, 2026)
This study aims to analyze the influence of work environment, service, customer satisfaction on employee performance at Coffee Shop Geko Medan City. The research sample was 30 respondents. Based on the results of the t hypothesis test, it can be concluded that work environment, service and customer satisfaction have a significant effect on employee performance. Based on the results of the F hypothesis test, it can be concluded that simultaneously/together work environment, service and customer satisfaction on employee performance with an Fcount 39.713 > Ftable 2.975 and a significance value of 0,000 < 0,05. Based on the analysis of the coefficient of determination, the coefficient of determination or Adjusted R-Square value of 0.800 or 80% of work environment, service and customer satisfaction on employee performance, while 20% is the influence of other variables that did not participate in this study.